- #1

- 96

- 0

my solution:

switch is closed so current begins to build up according to equation:

i = (E(bat)/R) (1-e^(-t/τ) )

multiplying R on both sides and plugging in for t = 2τ:

E(L) = E(bat) (1-e^(-2) )

E(L) / E(bat) = 1-e^(-2) ≈ 0.865

But my book says the answer is 0.135, which is just the value of e^(-2), which you would obtain if you used the equation for current decay

i = (E(bat)/R) (e^(-t/τ))

instead of the equation for current rise. But the current in this case is clearly rising. So is my book wrong or am I wrong?